Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Jarosite residues recycling by slurry electrolysis: Iron recovery and detoxification in one step - Rong Wang; Mengjun Chen; Wei Fan; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Process Safety and Environmental Protection, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Advances on jarosite residue detoxification and reutilization: a review - Mengjun Chen; Rong Wang; Wei Fan; Jiqin Wang; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Environmental Science and Pollution Research, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Behaviour of bamboo scrimber I-beam-box-column connections under static loads - Shao-Bo Kang; Jie-Xin Ding; Jun Xiong; Shu-Rong Zhou; Bin Long (Engineering Structures, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Functional insights of a two-component system sensor kinase GacS in a fish pathogen, Pseudomonas plecoglossicida - Su-Ming Zhou; Yan Wang; Feng-Ling Shu; Zhen Tao; Xiao Xie; Jia-Song Xie; Rong-Rong Ma; Fei Yin (Aquaculture, 2023)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Candida glabrata-Induced Refractory Infectious Arthritis: A Case Report and Literature Review - Shu Chen; Yi Chen; Yi-qin Zhou; Ning Liu; Rong Zhou; Jin-hui Peng; Qi-rong Qian (Mycopathologia, 2019)

Analysis of slight precipitation in China during the past decades and its relationship with advanced very high radiometric resolution normalized difference vegetation index - Xinyue Li; Yves Balkanski; Zhengfang Wu; Thomas Gasser; Philippe Ciais; Feng Zhou; Laurent Li; Shu Tao; Shushi Peng; Shilong Piao; Rong Wang; Tao Wang; et al. (International Journal of Climatology, 2018)
Precipitation is one of the most important factors determining the occurrence of extreme hydro‐meteorological events and water resource availability. Precipitation in different grades has diverse ecological effects, and slight precipitation (SP, defined as 0.1–1.0 mm/day) is the minimal level among them. In this study, we investigated SP trends from 1961 to 2013, as well as the relationship between SP and advanced very high radiometric resolution (AVHRR) normalized difference vegetation index (NDVI) in China during growing season from 1981 to 2006. The distributions and trends of SP were analysed by calculating the daily precipitation data. The average annual slight precipitation amount (SPA) and the number of slight precipitation days (SPD), derived from 839 monitoring stations in China, show a decreasing trend over the last five decades, which is in agreement with total precipitation (TP) but in different rates. When the trend was analysed seasonally, SP in most stations decreases significantly in September–October–November (SON) and June–July–August (JJA), and the largest decrease is found in SON. About 49.5 and 68.7% of monitoring stations show a decreasing trend in SON, in both SPA and SPD, whereas the trend is less popular in March–April–May (MAM, SPA: 19.7%, SPD: 41.4%) and December–January–February (JJF, SPA: 25.6%, SPD: 43.1%). Moreover, our analysis indicates that the decrease of SP is mainly due to the decrease of SPD as the median amount of daily SP was unchanged over the past five decades (close to 0.3 mm/day). Based on 26‐year (1981–2006) semi‐monthly AVHRR NDVI data and the records of SP data, the relationship between AVHRR NDVI and SP was also investigated. In regions with lower (

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Global forest carbon uptake due to nitrogen and phosphorus deposition from 1850 to 2100 - Rong Wang; Daniel Goll; Yves Balkanski; Didier Hauglustaine; Olivier Boucher; Philippe Ciais; Ivan Janssens; Josep Penuelas; Bertrand Guenet; Jordi Sardans; Laurent Bopp; Nicolas Vuichard; et al. (Global Change Biology, 2017)
Spatial patterns and temporal trends of nitrogen (N) and phosphorus (P) deposition are important for quantifying their impact on forest carbon (C) uptake. In a first step, we modeled historical and future change in the global distributions of the atmospheric deposition of N and P from the dry and wet deposition of aerosols and gases containing N and P. Future projections were compared between two scenarios with contrasting aerosol emissions. Modeled fields of N and P deposition and P concentration were evaluated using globally distributed in situ measurements. N deposition peaked around 1990 in European forests and around 2010 in East Asian forests, and both increased sevenfold relative to 1850. P deposition peaked around 2010 in South Asian forests and increased 3.5‐fold relative to 1850. In a second step, we estimated the change in C storage in forests due to the fertilization by deposited N and P (∆C ν dep ), based on the retention of deposited nutrients, their allocation within plants, and C:N and C:P stoichiometry. ∆C ν dep for 1997–2013 was estimated to be 0.27 ± 0.13 Pg C year −1 from N and 0.054 ± 0.10 Pg C year −1 from P, contributing 9% and 2% of the terrestrial C sink, respectively. Sensitivity tests show that uncertainty of ∆C ν dep was larger from P than from N, mainly due to uncertainty in the fraction of deposited P that is fixed by soil. ∆ C P dep was exceeded by ∆ C N dep over 1960–2007 in a large area of East Asian and West European forests due to a faster growth in N deposition than P. Our results suggest a significant contribution of anthropogenic P deposition to C storage, and additional sources of N are needed to support C storage by P in some Asian tropical forests where the deposition rate increased even faster for P than for N.

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Cloning and Characterization of KLHL5, a Novel Human Gene Encoding a Kelch-Related Protein with a BTB Domain - Shu Wang; Zongxiang Zhou; Kang Ying; Rong Tang; Yan Huang; Chaoqun Wu; Yi Xie; Yumin Mao (Biochemical Genetics, 2001)